Nonalcoholic fatty liver disease is independently associated with an increased incidence of cardiovascular disease in adult patients with type 1 diabetes. (15th December 2016) - Mantovani, Alessandro; Mingolla, Lucia; Rigolon, Riccardo; Pichiri, Isabella; Cavalieri, Valentina; Zoppini, Giacomo; Lippi, Giuseppe; Bonora, Enzo; Targher, Giovanni
Abstract: Background: Recent studies suggested that nonalcoholic fatty liver disease (NAFLD) is associated with an increased prevalence of cardiovascular disease (CVD) in type 1 diabetes. We assessed whether NAFLD also predicts the risk of incident CVD events in type 1 diabetic adults. Methods: We studied a retrospective cohort of 286 type 1 diabetic outpatients (mean age 43 ± 14 years; median duration of diabetes 17 [10–30] years) without secondary causes of chronic liver diseases, who were followed for a mean period of 5.3 years for the occurrence of incident CVD events (a combined endpoint inclusive of nonfatal ischemic heart disease, nonfatal ischemic stroke or coronary/peripheral artery revascularizations). NAFLD was diagnosed by ultrasonography. Results: Overall, 150 patients (52.4%) had NAFLD at baseline. During a mean follow-up of 5.3 ± 2.1 years, 28 patients developed incident CVD events. Patients with NAFLD had a higher incidence of CVD events than those without NAFLD (17.3% vs. 1.5%, p < 0.001). NAFLD was associated with an increased risk of CVD events (hazard ratio [HR] 8.16, 95% confidence interval [CI] 1.9–35.1, p < 0.005). Adjustments for age, sex, body mass index, smoking, diabetes duration, hemoglobin A1c, dyslipidemia, hypertension, chronic kidney disease, prior ischemic heart disease and serum gamma-glutamyltransferase levels did not appreciably attenuate the association between NAFLD and incident CVD (adjusted-HR 6.73, 95% CI 1.2–38.1, p = 0.031). Conclusions: This is the first observational study to demonstrate that NAFLD is associated with an increased risk of incident CVD events in type 1 diabetic adults, independently of established CVD risk factors and diabetes-related variables. Highlights: NAFLD is an emerging risk factor for CVD both in patients with type 2 diabetes and in those without diabetes. There are no published data in the literature on the association between NAFLD and risk of incident CVD events in patients with type 1 diabetes. This is the first observational study to show that ultrasound-diagnosed NAFLD is associated with an approximately 8-fold increased risk of incident CVD events in type 1 diabetic adults. This association remains significant even after adjustment for traditional cardiovascular risk factors and diabetes-related variables.